Countering Disinformation on Social Media Platforms: Developments in the EU and Poland - Kulesza, Joanna; Burdiak, Pavlo (Mediaforum : Analytics, Forecasts, Information Management, 2023)
One of the biggest challenges to European democracies is the spread of malicious disinformation, facilitated by the increasing importance of online platforms as news sources. The present article sheds light on the initiatives to combat disinformation on social media platforms in the EU. Some insights from Poland are also drawn.The research reveals that the EU’s anti-disinformation activities can be traced back to 2015, which marked the establishment of the East StratCom Task Force, disinformation monitoring project EUvsDisinfo, and Hybrid Fusion Cell. Building on these initiatives, the EU prompted the development of a groundbreaking self-regulatory Code of Practice on Disinformation, followed up and complemented by the legally binding DSA. Both documents provide due diligence standards and promote best practices for combating disinformation on platforms.With regard to the developments in Poland, notwithstanding some legislative proposals the country lacks comprehensive national policies to address platform disinformation. It persists as a critical concern, exacerbated by the rule of law challenges since 2015.The article recommends complementing well-elaborated legal frameworks with media literacy initiatives, civil society engagement, and technological innovations to detect and counter disinformation more efficiently. Such a holistic approach can enhance society’s resilience against disinformation while upholding democratic principles and freedom of expression in the digital age.